Impact of Hashimoto’s thyroiditis on ultrasound diagnosis of papillary thyroid carcinoma: a retrospective study - Teng, Chao; Pang, Kunkun; Zhang, Lulu; Li, Yuan; Wei, Xiuliang; Zhang, Feixue (Frontiers in Oncology, 2025)
ObjectiveTo investigate the clinical features and ultrasonic manifestations of papillary thyroid carcinoma (PTC) with Hashimoto’s thyroiditis (HT) and without HT. The characteristics were analyzed to improve the accuracy of diagnosing PTC with HT via ultrasound, potentially reducing overtreatment in certain cases.MethodsThe patients were retrospectively analyzed in the Second Hospital of Shandong University from December 2015 to January 2020. A total of 5732 patients had thyroid nodules on ultrasound. Among them, 553 patients (702 nodules) received surgical treatment and the histopathological results showed PTC with or without HT were enrolled. Univariate and multivariate analyses were conducted to evaluate the risk factors associated with HT influencing the ultrasound diagnosis of PTC. The nodules were categorized into two groups based on pathological results: PTC with HT and PTC without HT.ResultsGender, nodule echo, posterior echo change, border, aspect ratio, and nodule invasion rate significantly differed between the two groups (P<0.05). Independent variables for the multivariate logistic regression model were selected from those that showed statistical significance (P<0.05) in the univariate analysis. The results showed that the model was statistically significant (χ2 = 4.717, P<0.001, R2 = 0.185). Being female and aspect ratio ≥1 were identified as the risk factors for the diagnosis of PTC with HT, and the values were higher in group A than in group B by 3.15 and 1.73, respectively (OR=3.15, 1.73, P<0.05). Moreover, HT was identified as the protective factor because PTC was less likely to invade the thyroid capsule than the control group (OR=0.47, P<0.05).ConclusionsHT can affect the clinical and ultrasonographic features of PTC in distinct ways. It provides a protective effect on the capsule, significantly reducing capsular invasion, while female gender and an aspect ratio ≥1 are associated with an increased risk of PTC with HT diagnosis.